ANALYZING THE EFFECTF QUALITY OF FOOD, SERVICE, AND PHYSICAL ENVIRONMENT ON CUSTOMER SATISFACTION CASE STUDY OF CABAL DINING - Tanjaya, Stevany Carolin (Sam Ratulangi University, 2015)
ABSTRACT The primary needs of food resulted in booming of culinary industry. Recently, in Manado city, the culinary business is growing rapidly. Customer satisfaction is the most fundamental asset in this industry because it is the key to sustainable competitive advantage. The study aims: (1) To identify the effect of Quality of Food, Service and Physical Environment on Customer Satisfaction simultaneously, (2) To identify the effect of Quality of food on Customer Satisfaction partially, and (3) To identify the effect of Service Quality on Customer Satisfaction partially, (4) To identify the effect of Physical Environment on Customer Satisfaction partially. 130 people of Manado city by incident sampling randomly were surveyed as respondents. The result shows that food quality has a significant influence to customer satisfaction, service quality has a significant effect to customer satisfaction, and physical environment has a significant effect to customer satisfaction. Â Keywords: Food Quality, Service Quality, Physical Environment Quality, Customer Satisfaction